Employees of the future beware: How what is shared on social networks can affect job applications. Issue 3 (9th May 2016) - Linacre, Simon
Abstract : Purpose: The purpose of this paper is to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Is the art of writing a good CV dying? Never has it been easier to bypass the traditional form of proving one's credentials for work, with the Internet fast-tracking all manner of ways to show how good any individual may be at their work. Videos can show in real time someone performing their job; references can be emailed in an instant; online sites can host qualifications and recommendations; and there are even virtual badges and other accreditations that can be pinned to the virtual chest of any applicant. Surely, employers have never had it so good when it comes to recruitment. Practical implications: This study provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.